Criteria of prescription of antibiotics and systemic corticosteroids among pulmonologists and general practictioners during asthma and COPD exacerbations: a southern Italian survey - Dragonieri, Silvano; Carratu, Pierluigi; Ranieri, Teresa; Carpagnano, Giovanna Elisiana; Resta, Onofrio (Acta Biomedica Atenei Parmensis, 2021)
To date, there is still a lack of unanimity regarding the definition of exacerbation of asthma and COPD and about objective measurements in the currently used criteria. The aim of our study was to conduct a survey among general practitioners (GPs) and pulmonologists regarding the clinical criteria arbitrarily considered as important to start a course of systemic corticoids and/or antibiotics in asthma and COPD. We conducted a survey enrolling 50 general practitioners (GPs) and 50 pulmonologists, that evaluated the clinical criteria arbitrated as essential to start a course of systemic corticosteroids or antibiotics during asthma and/or COPD exacerbations. Our results demonstrated incongruities between GPs and pulmonologist and within the same professional category concerning systemic corticosteroids. Conversely, we showed higher consensus between and within the groups about criteria to prescribe antibiotics.